The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/eat.22056
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on thin‐ideal internalization

Abstract: Objective Current research on the etiology of thin-ideal internalization focuses on psychosocial influences (e.g., media exposure). The possibility that genetic influences also account for variance in thin-ideal internalization has never been directly examined. This study used a twin design to estimate genetic effects on thin-ideal internalization and examine if environmental influences are primarily shared or nonshared in origin. Method Participants were 343 post-pubertal female twins (ages 12–22; M=17.61) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 60 publications
(87 reference statements)
0
27
1
1
Order By: Relevance
“…Furthermore, results indicated that momentary thin-ideal importance was associated with momentary body dissatisfaction, above and beyond the influence of simply thinking about appearance, providing further justification for the existence of a state-based component of internalization. These findings thus challenge the notion that thin-ideal internalization is a static construct (e.g., Colautti et al, 2011; Suisman et al, 2012). Rather and in line with Karazsia et al (2013), it appears that thin-ideal internalization can be at least somewhat activated or downplayed in the moment, likely due to contextual factors (e.g., attention paid to thin-ideal stimuli; Brown & Dittmar, 2005), which should be explored further in future studies.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Furthermore, results indicated that momentary thin-ideal importance was associated with momentary body dissatisfaction, above and beyond the influence of simply thinking about appearance, providing further justification for the existence of a state-based component of internalization. These findings thus challenge the notion that thin-ideal internalization is a static construct (e.g., Colautti et al, 2011; Suisman et al, 2012). Rather and in line with Karazsia et al (2013), it appears that thin-ideal internalization can be at least somewhat activated or downplayed in the moment, likely due to contextual factors (e.g., attention paid to thin-ideal stimuli; Brown & Dittmar, 2005), which should be explored further in future studies.…”
Section: Discussioncontrasting
confidence: 51%
“…Thin-ideal internalization has generally been described as “trait-like” in the literature (e.g., Colautti et al, 2011; Suisman et al, 2012), but we found there was moment-to-moment variability in individuals’ reports of one aspect of this construct, thin-ideal importance. Furthermore, results indicated that momentary thin-ideal importance was associated with momentary body dissatisfaction, above and beyond the influence of simply thinking about appearance, providing further justification for the existence of a state-based component of internalization.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…If genetic selection effects play a role, this could be via heritable personality traits, such as perfectionism, which have been hypothesized to contribute to genetic risk for thin-ideal internalization (Suisman et al, 2012). Indeed, these same traits may also contribute to peer group selection (i.e., girls similar in personality may be more likely to form friendships with one another).…”
Section: Discussionmentioning
confidence: 99%
“…Given significant associations between BMI and thin-ideal internalization (Suisman et al, 2012, 2014), as well as evidence for clustering of BMI among friend groups (Fletcher et al, 2011), BMI was used as a covariate in all analyses. BMI was calculated ([weight])/[height] 2 ) from measures of height and weight made using a wall-mounted ruler or tape measure and digital scale, respectively.…”
Section: Methodsmentioning
confidence: 99%